The influence of exercise on body esteem among college students of different genders: evidence from Latin dance and aerobics - Hu, Yuna; Zeng, Yong; Dong, Heling; Li, Han (Frontiers in Psychology, 2025)
BackgroundBody esteem is pivotal to college students’ psychological well-being. Evidence suggests Latin dance and aerobics can enhance body image, but comparative, gender-specific effects remain underexplored.MethodsIn a 12-week randomized controlled trial, students (N = 90; 45 men, 45 women) were assigned to Latin dance group (LDG), aerobics group (AG), or control group (CG). Body esteem was assessed pre- and post-intervention using PSPP subscales: sport competence (SC), physical condition (PC), body attractiveness (BA), physical strength (PS), and general physical self-worth (PSW). Statistical analyses included independent sample t-tests, paired sample t-tests, and ANOVA.ResultsBoth LDG and AG improved overall body esteem versus CG (p < 0.05). Compared with CG, LDG produced greater gains in BA and SC (p < 0.05), with significant benefits among female participant (BA, SC: p < 0.05). AG produced larger improvements in PC and PS versus CT (p < 0.05), with significant gains among male participant (PS: p < 0.01; PC: p < 0.05). No between-group differences were observed for PSW (LDG vs. AG, ns).ConclusionThis study indicates that both Latin dance and aerobics effectively enhance body esteem among college students but through distinct mechanisms. Latin dance particularly improves emotional and social dimensions of body esteem, offering pronounced benefits for female participant, while aerobics primarily enhances physical fitness aspects, more effectively benefiting male participant. These findings underscore the importance of providing diverse exercise modalities in university wellness programs to cater to varied gender-specific psychological and physical health needs.Clinical trial registrationChiCTR25063201.